Transadaptation and validation of dysphagia handicap index in Bangla - Pal, Paramita; Chatterjee, Indranil (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: The aim of this study was to transadapt and validate the Bangla version of DHI (DHI-B). The objective of the study was to translate and culturally adapt the Dysphagia Handicap Index (DHI) in Bangla language. Methods: Thirty individuals (mean age-42.23, SD±12.52) with dysphagia and an equal number of healthy individuals (mean age-28.23, SD±10.68) participated to fill up the questionnaire of DHI-B. Establishment of validity was done by comparing DHI-B scores of healthy controls and patients with dysphagia. Test–retest reproducibility, content validity and concurrent validity were established and internal consistency were used for reliability testing. Results: The overall Cronbach’s α for DHI-B was 0.84, indicating good internal consistency. Pearson’s correlation on test–retest reliability of DHI-B was found to be 0.9. Correlation that achieved between subscales of DHI-B and total DHI-B was analysed using Pearson’s correlation which was found very high. Compared to the dysphagic group, the control group showed significantly lower scores for all scales. Conclusion: From this study it was concluded that DHI-B showed good internal consistency, test-retest reliability, and concurrent validity. Therefore, it could be claimed that for assessment of dysphagia related handicap in Bangla, DHI-B is a reliable and valid tool.